Permasalahan Pembelajaran PAI di Kalangan Peserta Didik Di Era Global - Nur Hasanah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The globalization era has brought significant impacts on various aspects of life, including Islamic religious education (PAI). This research aims to identify and analyze the problems faced in PAI learning among students in the global era. The research method used is [research method - to be adjusted according to actual research]. The research results show that PAI learning in the global era faces various complex challenges, including: negative influences of technology and social media, religious identity crisis among students, gaps between traditional Islamic values and modernity, lack of innovative and relevant learning methods, and insufficient teacher competencies in integrating technology in PAI learning. Other findings indicate a decline in student interest and motivation toward religious learning, as well as difficulties in understanding the relevance of Islamic teachings to contemporary life. This research recommends the need for more contextual PAI curriculum reform, improvement of educator competencies, integration of appropriate learning technologies, and strengthening of learning approaches that can bridge Islamic values with the demands of the global era.